Pilot study of sex differences in QTc intervals of heart transplant recipients - Novotny, Tomas; Leinveber, Pavel; Hnatkova, Katerina; Reichlova, Tereza; Matejkova, Magdalena; Sisakova, Martina; Krejci, Jan; Hude, Petr; Bedanova, Helena; Nemec, Petr; Spinar, Jindrich; Spinarova, Lenka; et al. (Journal of electrocardiology, 2014)
Repolarization processes in female and male are different. This study provided pilot data on automatic measurements of QT intervals in heart transplant (HT) recipients stratified according to the sex of the recipient and the donor. The following groups were analyzed: Group A—20 males with male heart, group B—14 females with male heart, group C—13 females with female heart, group D—11 males with female heart, group E—20 healthy males, and group F—20 healthy females. Twelve-lead electrocardiograms were digitally captured during autonomic provocative test of five postural 8-minute stages—supine, unsupported sitting, supine, unsupported standing, and supine. Fridericia formula was used for heart rate correction together with a generic correction for QT/RR hysteresis. Neither female nor male HT recipients exhibit any differences in QTc interval duration related to the sex of the donor. There was, however, a trend towards longer QTc intervals in female HT recipients compared to male HT recipients irrespective of the sex of the donor. The QTc differences between healthy control females and males were highly statistically significant proving the assay sensitivity of the study. The available pilot data suggest that in HT patients, the sex of the donor has little influence on the QTc interval of the transplanted heart.